Optimization on Operation Parameters in Reinforced Metal Matrix of AA6066 Composite with HSS and Cu. (2nd July 2021) - Sesharao, Y.; Sathish, T.; Palani, Kumaran; Merneedi, Anjibabu; L, Natrayan; De Poures, Melvin Victor; Maridurai, T.
Abstract : This optimization investigation focused on the reinforced metal matrix composite of aluminium alloy. Novel of this work is to fabricate the AA6066 composite with HSS and Cu, continually conduct machining tests, and evaluate the tool wear, surface roughness, and thrust force of the stir-casted specimens. The aluminium composite has 90 percentage of AA6066 alloy reinforcement with six percentage of high-speed steel and four percentage of copper alloy made by the casting method. The fabricated composites' turning parameters were optimized through the Taguchi method. The turning operation can be done with the help of the normal lathe with the CBN insert tool. The operation parameters such as feed, depth of cut, and steam pressure of the cutting fluid were considered with three different equal intervals in each parameter. In this investigation, the L9 orthogonal array method is used to identify the optimum values of the turning parameters among the considered machining parameters concerning the response such as wear on the turning tool and thrust forces created on machining. The outcome based on the parameters was identified and mentioned as the rank order for individual and combination of all responses with different conditions. Then, the separate and combined optimized input parameters were provided as the conclusion.